2019
DOI: 10.1002/ps.5520
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective bioactivity, toxicity and degradation of the chiral triazole fungicide bitertanol

Abstract: BACKGROUND The chiral pesticide bitertanol has been widely used in the prevention and treatment of fungal diseases on many crops. However, research on bitertanol at the stereoisomer level has not been reported. Here, we study the stereoselective bioactivity, toxicity, and degradation of this pesticide under laboratory and field conditions. RESULT (1S,2R)‐Bitertanol was the most effective stereoisomer, showing 4.3–314.7 times more potent bioactivity than other stereoisomers against eight target pathogenic fungi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…For example, (R)‐flufiprole is better able to block the passage of chloride ions in the γ‐aminobutyric acid receptor, which resulted in a higher bioactivity of (R)‐flufiprole than (S)‐flufiprole toward agricultural pests . The stereoselective bioactivity of bitertanol stereoisomers correlated with the binding distance and calculated energy difference between the stereoisomers and the target protein . In this study, bromothalonil enantiomers exhibited distinct inhibitory activities against different fungal species.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…For example, (R)‐flufiprole is better able to block the passage of chloride ions in the γ‐aminobutyric acid receptor, which resulted in a higher bioactivity of (R)‐flufiprole than (S)‐flufiprole toward agricultural pests . The stereoselective bioactivity of bitertanol stereoisomers correlated with the binding distance and calculated energy difference between the stereoisomers and the target protein . In this study, bromothalonil enantiomers exhibited distinct inhibitory activities against different fungal species.…”
Section: Resultsmentioning
confidence: 69%
“…22 The stereoselective bioactivity of bitertanol stereoisomers correlated with the binding distance and calculated energy difference between the stereoisomers and the target protein. 23 In this study, bromothalonil enantiomers exhibited distinct inhibitory activities against different fungal species. Especially, bromothalonil enantiomers showed the opposite inhibitory effects against C. cliviicola and C. musae, both of which belong to the Colletotrichum spp.…”
Section: Stereoselective Fungicidal Activity Of Bromothalonilmentioning
confidence: 71%
“…Therefore, the antifungal activity of pydiflumetofen may be derived mainly from the R enantiomer. Li et al 31 reported that (1R,2R)-bitertanol and (1S,2R)bitertanol exhibited higher activity than (1S,2S)-bitertanol and (1R,2S)-bitertanol on all pathogens by a factor of 4.3-314.7 times. Dong et al 32 reported that a 24.2-fold difference in bioactivity was found between difenoconazole enantiomers.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its antibacterial effects, studies have also examined its residues on fruits and vegetables using an achiral analytical method (Farha et al., 2016; JMPR, 2008; H. Zhang et al., 2014). However, some cases have already shown that achiral research results of chiral fungicides cannot accurately describe their biological activity, toxicity, metabolites, and environmental behavior because pure enantiomers tend to display different properties in biological systems due to their stereostructural differences (Dong et al., 2013; Kaziem et al., 2020; Li et al., 2019; Li et al., 2020; Liang et al., 2020; Pan et al., 2018; Zhang et al., 2015). Therefore, research on mandipropamid at the enantiomer level is crucial.…”
Section: Introductionmentioning
confidence: 99%